Integrated maintenance management model in the printing industry - Horváth, Csaba (Journal of Graphic Engineering and Design, 2023)
Rapid technological and economic changes are setting radically new task for maintenance divisions of printing works. In this dissertation the author provides a summary on the possible approaches for the adoption to the new requirements. He formulates his situation analysis based on an exhaustive questionnaire survey, and points out the currents of changes and challenges caused by the expected developments in the maintenance field of the printing industry. Based on the possible answers on these challenges, the Author has compiled a - yet missing - maintenance management model that encompasses the maintenance specialties of the industry, as well as the professional heritage and the latest scientific accomplishments in the discipline of maintenance. The model is based on the widely accepted quality focused maintenance approach, that is supplemented by the Author with four new aspects - 1) reliability-focused culture, 2) quality management system, 3) employment of external service provides, 4) maintenance characteristics specific to printing machinery - determining their effects and integrating them into one single system. In order to construct the model, the Author develops specific solutions that can be seen as own scientific achievements on the specification of maintenance characteristics of printing machinery; on the efficiency improving applications of quality management systems, modern knowledge management and reliability focused corporate culture; and on the implementation of a maintenance information system.